Frog on a log? - Gray, Kes; Field, Jim, 1980- (New York, NY : Scholastic Press, 2015)
In rhyming text, cat explains why frog has to sit on a log, even if he finds it uncomfortable.
"Frog on a Log? was originally published in the U.K. by Hodder Children's Books, a division of Hachette Children's Books, under the title Oi Frog!"
Keywords: Frogs -- Juvenile fiction; Cats -- Juvenile fiction; Stories in rhyme; Stories in rhyme; Frogs -- Fiction; Cats -- Fiction; Animals -- Fiction